Physiological races of Puccinia triticina E. identified in the North of Sinaloa and germplasm resistance - Rodríguez García, María Florencia; García León, Elizabeth; Huerta Espino, Julio; Villaseñor Mir, Héctor Eduardo; Llaven Valencia, Genny; González González, Miguel (Revista Mexicana de Ciencias Agrícolas, 2020)
Leaf rust caused by Puccinia triticina E. is the most important disease in the North and Northwest of Mexico. In the North of Sinaloa, it is widely distributed in the wheat production areas of Valle del Fuerte and Valle del Carrizo; however, it is unknown which races are influencing that region. The objective was to identify the physiological races of leaf rust, which occur in the main producing areas of Northern Sinaloa, and to identify germplasm with resistance. During the autumn-winter 2018-2019 crop cycle, 50 samples of leaf rust were collected from experimental and commercial lots, these samples were transferred to Lanarec. With the monopostular technique, the identification of races was carried out. Subsequently, with the most frequent races, 35 bread wheat genotypes were evaluated under greenhouse conditions and for their resistance in seedlings and adult plants. Seven physiological races of leaf rust were identified (CBJ/QQ, MBT/SP, MCT/SP, MGJ/SP, MBJ/SP, MBJ/QQ, MFJ/SP), of which CBJ/QQ was identified with higher frequency (29%). Of the 35 genotypes evaluated with the CBJ/QQ and MCT/SP races, it was determined that CONATRIGO F2015 and the lines CHEWINK #1/MUTUS//MUTUS*2/HARIL#1 and MUTUS*2//ND643/2*WBLL1/3/BORL14 were resistant in seedling and adult plant to both races, which indicates that it possesses at least one gene for effective resistance to leaf rust. Genetic resistance is one of the most viable sustainable management alternatives for the control of wheat rusts in Mexico.